Accelerating the rate of genetic value creation for East and South African smallholder maize farmers - CGIAR Research Program on Maize (2020)
Maize breeding creates value for farmers by delivering varieties which provide stable and improved harvests. The MAIZE breeding team adapted genomic technologies to improve the efficiency of the breeding process, to deliver more value to African small holder maize farmers per unit of investment, by reducing the cost of first year field evaluation by 40%. Current and future innovations applying genomic technology to breeding pipelines will increase CGIAR and eastern and southern African maize breeding programs' precision and efficiency.